Certification of Agri-Food Products for Sale - Cristina M. STERIE; Daniela POPA; Marian MOTOFEANU; Marian MOTOFEANU (Communications of International Proceedings, 2021)
The certification of agri-food products represents the commitment of the producers to ensure the quality of the product, the process offering a superior character to all the attributes of the product. The main feature of certified products is the quality, which is reflected both by raw materials, the production chain, and by the finished product that aims to meet consumer expectations, providing the maximum guarantee of product safety. The products must be certified to be marketed with the quality marks that consumers trust. Recently, Romania has allocated significant funding for Romanian products to be included in one or more quality schemes to increase their notoriety. The aim of the research is to identify the perception of Romanian consumers regarding these products, but especially if this type of product influences their decision to purchase certified agri-food products, to the detriment of the usual ones. The results obtained from the use of the survey method based on the questionnaire, indicate a degree of confusion regarding food quality schemes, a share of over 44% of respondents consider that these quality schemes are profitable for consumers, in time what 43% of them consider to be beneficial for consumers.
Keywords: Certification; Marketing; Agri-Food; Romania.